2003
DOI: 10.1074/jbc.m302663200
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Sweetness of Variants of the Protein Brazzein with Patterns of Hydrogen Bonds Detected by NMR Spectroscopy

Abstract: C atoms were collected from the six brazzein proteins labeled uniformly with carbon-13 and nitrogen-15. In wild-type brazzein, this approach identified 17 backbone hydrogen bonds. In the mutants, altered magnitudes of the couplings identified hydrogen bonds that were strengthened or weakened; missing couplings identified hydrogen bonds that were broken, and new couplings indicated the presence of new hydrogen bonds. Within the series of brazzein mutants investigated, a pattern was observed between sweetness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Two arginines (R33 and R43) were shown to be important for brazzein’s sweetness 34. Mutant R43A was shown to exhibit profoundly reduced sweetness (only slightly sweet in powder form) 34; 42. R43 is part of the critical Site 1 loop (Loop43) further investigated here by mutagenesis, biochemical studies, and human taste trials.…”
Section: Discussionmentioning
confidence: 90%
“…Two arginines (R33 and R43) were shown to be important for brazzein’s sweetness 34. Mutant R43A was shown to exhibit profoundly reduced sweetness (only slightly sweet in powder form) 34; 42. R43 is part of the critical Site 1 loop (Loop43) further investigated here by mutagenesis, biochemical studies, and human taste trials.…”
Section: Discussionmentioning
confidence: 90%
“…Extensive libraries of sweeteners (e.g., Spillane et al 2006) could now be examined for their ability to bind and activate human or cross-species chimeric receptors, elucidating key determinants for sweetener-receptor interactions. The relatively straightforward structural analysis of sweet protein mutants (Assadi-Porter et al 2003 ;De Simone et al 2006 ;Esposito et al 2006 ;Hobbs et al 2008 ;Spadaccini et al 2003) suggests that they may be particularly informative for understanding how changes in sweetener structure impact sweetener efficacy.…”
Section: Structure-activity Relationships For Sweeteners: Comingmentioning
confidence: 99%
“…Mutagenesis studies suggest that the major sites of brazzein's interactions with the sweet receptor are nearby loop 43 and the N-and C-terminal regions of brazzein (Assadi-Porter, Aceti, & Markley, 2000). Mutagenesis and NMR studies have also suggested that residues 29-33 and 39-43 in the loops are involved in the sweetness of brazzein and play an important role in the interaction between brazzein and the sweet-taste receptor (Assadi-Porter, Abildgaard, Blad, & Markley, 2003;Assadi-Porter et al, 2005;Jin et al, 2003). In addition, significant contributions to brazzein's sweetness were also made nearby loop 33 and loop 9-19.…”
Section: Introductionmentioning
confidence: 96%